تأثير موعد الزراعة والتراكيز المختلفة من حمض أندول بيوتريك (IBA) في تجذير عقل الكيوي ( Actinidia chinensis) المتخشبة - محفوض, محمد; مخول, جرجس; محمد, ناصر (Latakia University Journal -Biological Sciences Series, 2018)
تضمنت الدراسة عاملين رئيسين: 1- تأثير مواعيد أخذ العقل وزراعتها في نسبة التجذير ونوعية الغراس الناتجة لصنف الكيوي Hayward. 2- تأثير تراكيز مختلفة من حمض أندول بيوتريك (IBA) في نسبة العقل المجذرة ونوعية الغراس المنتجة. بينت الدراسة أن الموعد الثاني (منتصف شهر شباط) أعطى أعلى نسبة تجذير في كافة التراكيز المستخدمة، حيث بلغت حدها الأعظمي (91%) عند استخدام التركيزين 4000 و 5000 جزء بالمليون مقارنة بالموعدين الأول والثالث دون فروق معنوية بينهما، بينما أعطى الشاهد أقل نسبة تجذير (0%، 13.7%، 13.7%) في المواعيد الثلاث على التوالي وأردأ الغراس بدليل مجموعيها الخضري (10.36، 13.25 غرام) والجذري (1.60 و 3.17 غرام) على التوالي. كما أن أفضل الغراس الناتجة بدليل وزن المجموع الخضري الطازج ( 16.17 و 15.83 و21.04 غرام) والمجموع الجذري الطازج (2.97 و 3.77 و 5.93 غرام ) كانت عند استخدام التركيز العالي من حمض أندول بيوتريك (6000) جزء بالمليون وفي المواعيد الثلاثة المختبرة، وقد تفوق التركيز 6000 جزء بالمليون على كافة التراكيز الأخرى وبدلالة إحصائية واضحة. Two major factors have been included in this study: 1) The effect of cutting and planting dates of Kiwi cuts, variety Hayward, on percentage of rooting and the quality of plantlets. 2) The effect of various concentrations of IBA on the percentage of rooting and the quality of plantlets. This study showed that the highest percentage of rooting (91%) in all concentrations used (4000 PPM and 5000 PPM) was archived in the second date (Middle February) compared to the results of first and third dates. The control treatment gave the lowest plantlets quality, and the lowest percentage of rooting 0%, 13.7% and 13.7% in the three dates of cutting and planting, respectively. The worse plantlets as indicated by shoots growth were (10.36, 13.25) and Roots (1.60 and 3.17 g), respectively. Better plantlets quality in terms of vegetation weight (16.7, 15.83 and 21.04g) and root system weight (2.97, 3.77 and 5.93g) were obtained in the three tested dates when high concentration of IBA (6000 PPM) was applied; statistically, the concentration 6000 PPM was the best.